Heavy ion radiation exposure triggered higher intestinal tumor frequency and greater β-catenin activation than γ radiation in APC(Min/+) mice. - Kamal Datta; Shubhankar Suman; Bhaskar V S Kallakury; Albert J Fornace (PLoS ONE, 2013)
Risk of colorectal cancer (CRC) after exposure to low linear energy transfer (low-LET) radiation such as γ-ray is highlighted by the studies in atom bomb survivors. On the contrary, CRC risk prediction after exposure to high-LET cosmic heavy ion radiation exposure is hindered due to scarcity of in vivo data. Therefore, intestinal tumor frequency, size, cluster, and grade were studied in APC(Min/+) mice (n = 20 per group; 6 to 8 wks old; female) 100 to 110 days after exposure to 1.6 or 4 Gy of heavy ion (56)Fe radiation (energy: 1000 MeV/nucleon) and results were compared to γ radiation doses of 2 or 5 Gy, which are equitoxic to 1.6 and 4 Gy (56)Fe respectively. Due to relevance of lower doses to radiotherapy treatment fractions and space exploration, we followed 2 Gy γ and equitoxic 1.6 Gy (56)Fe for comparative analysis of intestinal epithelial cell (IEC) proliferation, differentiation, and β-catenin signaling pathway alterations between the two radiation types using immunoblot, and immunohistochemistry. Relative to controls and γ-ray, intestinal tumor frequency and grade was significantly higher after (56)Fe radiation. Additionally, tumor incidence per unit of radiation (per cGy) was also higher after (56)Fe radiation relative to γ radiation. Staining for phospho-histone H3, indicative of IEC proliferation, was more and alcian blue staining, indicative of IEC differentiation, was less in (56)Fe than γ irradiated samples. Activation of β-catenin was more in (56)Fe-irradiated tumor-free and tumor-bearing areas of the intestinal tissues. When considered along with higher levels of cyclin D1, we infer that relative to γ radiation exposure to (56)Fe radiation induced markedly reduced differentiation, and increased proliferative index in IEC resulting in increased intestinal tumors of larger size and grade due to preferentially greater activation of β-catenin and its downstream effectors.